Pengabdian Kepada Masyarakat Melalui Kuliah Kerja Nyata (Kkn) Di Rt.03 Kelurahan Pintu Batu Kota Bengkulu - Jopin, Jopin; Alpindi, Yeko; Pratama, Andhra Galih; Sulthon, Muhammad; Nanda, Bagus Putra; Tambunan, Dennis Rydarto; Putra, Dhanu Ario; Sumantri, Ajis (Jurnal Karya Nyata Pengabdian, 2026)
The absence of visual identity and administrative information centers at the neighborhood (RT) level often hampers regional coordination and public services for both residents and visitors. Community Service activities through the Student Community Service (KKN) of Dehasen University Bengkulu in RT 03, Pintu Batu Village, aim to strengthen regional administrative governance through the provision of physical information facilities. The implementation method included participatory observation, boundary mapping, and coordination with local neighborhood officials. The main focus of this program was the construction and installation of regional boundary signs to clarify physical boundaries between areas, as well as information boards containing professional data of RT 03 and RW 01 officials. The results of the activity showed that the installation of these facilities successfully created a clearer territorial identity, facilitated social-administrative navigation, and enhanced the professionalism of information services at the village level. This program is expected to serve as a model for more organized and informative environmental administration in other regions.